Kuala Lumpur Inner City Transport System (KLICTS) - Mohamad Zulhelmi, Man (2012)
Kuala Lumpur Inner City Transport System (KLICTS) is a new approach for public transport services that provide especially for people that want to plan journey at Kuala Lumpur inner city. This system involves public transport system worker and people want to use public transport services. They can use this system for manage their time and also to get important information for their journey such as ticket prices, schedule time and time estimate that will help them so that can more understand.This system created because of several problems and the main problem is the public transport services did not provide schedule or important information for public. So, that’s a reason for develop this system. Some public bus company provides schedule, but it is static schedule and sometime they not update the schedule. KLICTS developed by following System Development Life Cycle (SDLC) because it is as a model for developing a system based on a traditional problem-solving process with sequential steps and options for revisiting steps when problems appear. So, KLICTS created for help people that want plan their journey only in Kuala Lumpur inner city area so that easy and more clearly when want using public transport services.